Effects of Camphorquinone on Cytotoxicity, Cell Cycle Regulation and Prostaglandin E2 Production of Dental Pulp Cells: Role of ROS, ATM/Chk2, MEK/ERK and Hemeoxygenase-1. - Mei-Chi Chang; Li-Deh Lin; Min-Tsz Wu; Chiu-Po Chan; Hsiao-Hua Chang; Ming-Shu Lee; Tzu-Ying Sun; Po-Yuan Jeng; Sin-Yuet Yeung; Hsueh-Jen Lin; Jiiang-Huei Jeng (PLoS ONE)
Camphorquinone (CQ) is a popularly-used photosensitizer in composite resin restoration. In this study, the effects of CQ on cytotoxicity and inflammation-related genes and proteins expression of pulp cells were investigated. The role of reactive oxygen species (ROS), ATM/Chk2/p53 and hemeoxygenase-1 (HO-1) and MEK/ERK signaling was also evaluated. We found that ROS and free radicals may play important role in CQ toxicity. CQ (1 and 2 mM) decreased the viability of pulp cells to about 70% and 50% of control, respectively. CQ also induced G2/M cell cycle arrest and apoptosis of pulp cells. The expression of type I collagen, cdc2, cyclin B, and cdc25C was inhibited, while p21, HO-1 and cyclooxygenase-2 (COX-2) were stimulated by CQ. CQ also activated ATM, Chk2, and p53 phosphorylation and GADD45α expression. Besides, exposure to CQ increased cellular ROS level and 8-isoprostane production. CQ also stimulated COX-2 expression and PGE2 production of pulp cells. The reduction of cell viability caused by CQ can be attenuated by N-acetyl-L-cysteine (NAC), catalase and superoxide dismutase (SOD), but can be promoted by Zinc protoporphyin (ZnPP). CQ stimulated ERK1/2 phosphorylation, and U0126 prevented the CQ-induced COX-2 expression and prostaglandin E2 (PGE2) production. These results indicate that CQ may cause cytotoxicity, cell cycle arrest, apoptosis, and PGE2 production of pulp cells. These events could be due to stimulation of ROS and 8-isoprostane production, ATM/Chk2/p53 signaling, HO-1, COX-2 and p21 expression, as well as the inhibition of cdc2, cdc25C and cyclin B1. These results are important for understanding the role of ROS in pathogenesis of pulp necrosis and pulpal inflammation after clinical composite resin filling.